Pharmacokinetics, Safety, and Dosing of Novel Pediatric Levofloxacin Dispersible Tablets in Children with Multidrug-Resistant Tuberculosis Exposure - Garcia-Prats, Anthony J; Purchase, Susan E; Osman, Muhammad; Draper, Heather R; Schaaf, H Simon; Wiesner, Lubbe; Denti, Paolo; Hesseling, Anneke C (Antimicrobial agents and chemotherapy, 2019)
This study characterized the pharmacokinetics of novel 100-mg levofloxacin dispersible tablets in 24 children aged <5 years who had household multidrug-resistant tuberculosus (MDR-TB) exposure. The current data were pooled with previously published data from children ( = 109) with MDR-TB receiving adult (250-mg) levofloxacin tablets, using nonlinear mixed-effects modelling. The adult tablets had 41% lower bioavailability than the novel dispersible tablets, resulting in much higher exposures with the dispersible tablets with the same dose.